Learners' intrinsic motivation to participate in a political science program - Le, Thanh Thao; Nguyen, The Anh; Tran, Thi Phuong Huynh; Trinh, Quoc Lap (i-manager's journal on educational psychology, 2023)
In Vietnam, middle or high-ranking leaders and managers are required to have knowledge of politics. Those who hold leadership roles in both the private and public sectors should master a solid knowledge of political science. This study was conducted to learn about the intrinsic motivation of learners in Vietnam towards participating in an advanced political science program for future leaders. The study found that learners' intrinsic motivation to participate in a political science program is influenced by their interest in the subject matter, their belief in its relevance to their lives, and their desire to develop critical thinking skills. Additionally, the study identifies a number of factors that can enhance or detract from learners' intrinsic motivation, including teaching methods, course content, and assessment practices. A questionnaire designed with a quantitative method was used to collect data from 91 future leaders who were studying advanced politics at an academy of politics in Vietnam. The results show that they were highly motivated to participate in this program (M = 4.19). Perceived interest or enjoyment (M = 4.58), effort (M = 4.59), perceptions of the program values (M = 4.54), and relatedness (M = 4.54) were encouraging them to learn political science. Moreover, the learners did not experience any pressure or anxiety while taking part in this program (M = 2.46). This study shows that even though most people think political science is dry and mechanical, there are ways to keep learners motivated to learn.